2003
DOI: 10.1021/ac034451o
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Oxidation of p-Hydroxyphenylpyruvic Acid in Aqueous Solution by Capillary Electrophoresis with an Electrochemiluminescence Detection System

Abstract: A system of capillary electrophoresis with electrochemiluminescence detection (CE-ECL) together with UV spectroscopic and electrochemical methods were used to study the chemical oxidation of p-hydroxyphenylpyruvic acid (pHPP) by dissolved oxygen in aqueous solution. The pHPP was observed to be readily oxidized by dissolved oxygen in alkaline solution and yielded a compound that strongly enhanced the electrochemiluminescence of Ru(bpy)23+. This compound was separated and detected by a new CE-ECL system and reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13] McCall et al reported on the inhibition of Ru(bpy)3 2+ /TPrA ECL by phenol, substituted phenols, hyroquinones, catechols, and benzoquinones, and suggested a quenching mechanism involving benzoquinone derivatives formed at the electrode surface that quenches ECL via energy transfer. Li et al 12,13 observed the ECL of Ru(bpy)3…”
Section: +mentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] McCall et al reported on the inhibition of Ru(bpy)3 2+ /TPrA ECL by phenol, substituted phenols, hyroquinones, catechols, and benzoquinones, and suggested a quenching mechanism involving benzoquinone derivatives formed at the electrode surface that quenches ECL via energy transfer. Li et al 12,13 observed the ECL of Ru(bpy)3…”
Section: +mentioning
confidence: 99%
“…ECL using tris(2,2 0 -bipyridyl)ruthenium(II) (Ru(bpy) 3 21 ) has been extensively applied for the analysis of various compounds containing secondary or tertiary amine [21,22]. In recent years, ECL has attracted increasing interest as CE end-column detector for separation and detection of amine containing compounds and their derivatives for its high sensitivity, simple instrument and low assay cost [23][24][25][26][27][28][29][30][31]. Using an end-column electrode to convert Ru(bpy) 3 21 to active Ru(bpy) 3 31 form allows a simple and sensitive ECL detection scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the physiological and clinical significance, chemistry of pHPP has been a topic of constant interest. The methods for determination of pHPP included flow injection spectrophotometry combined with single chip microcomputer [3], fluorescence quenching [4], GC [5][6], HPLC [7], CE [8][9][10], and electrochemical technique [1]. The Keto-enol tautomerism of pHPP was early investigated by Chi et al, using electrochemical method and UV spectrometry [1].…”
Section: Introductionmentioning
confidence: 99%